Dietary supplements and medications in elite sport - polypharmacy or real need? - Suzic Lazic, J.; Dikic, N.; Radivojevic, N.; Mazic, S.; Radovanovic, D.; Mitrovic, N.; Lazic, M.; Zivanic, S.; Suzic, S. (Scandinavian Journal of Medicine & Science in Sports, 2011)
The aim of this study was to describe qualitatively and quantitatively dietary supplements (DS) and medication use in elite athletes. Athletes (n=912; age 23.9±6 years; 72% male) reported medications and DSs taken within 3 days before doping control. We analyzed data collected from 2006 to 2008, indentified and classified substances. Total of 74.6% athletes reported use of at least one substance, 61.2% took DS (3.17 per user) and 40.6% took medications. Among users, 21.2% reported the use of six and more different products, and one took 17 different products at the same time. Majority of medication users took non-steroidal anti-inflammatory drugs (NSAID) (24.7%), and 22.2% used more than one NSAID. We found no gender differences in DS use (P=0.83). Individual sport athletes used more DS (P<0.01). Our study showed widespread use of DS and drugs by elite athletes. Consumption of DS with no evident performance or health benefits, demonstrated the need for specific educational programs focused on DS use. Amount, quantity and combination of the reported products raised concern about the risk of potential side effects.